Assessment of Tummy Time Feeding on Fumbling and Plagiocephaly Head Shape in Infants - Widodo, Agus; Amithya, Farita Adhynda; Aditya, Ivan Fairuz; Ardiansyah, Faizin; Ma'nun, Arumi Lu'lul (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Tummy time is a form of physical activity recommended for infants less than 6 months of age that involves lying prone while awake on the floor, supervised by an adult. Regurgitation is a form of gastroesophageal reflux in infants where milk that has been swallowed comes out involuntarily. Plagiocephaly is an asymmetrical skull deformity caused by various factors that can be prevented to avoid aesthetic consequences. The purpose of this study was to determine the study of giving tummy time to spit up and plagiocephaly head shape. Methods: Cross-sectional study with survey method. Results: The results of data analysis of the spearman test used to test the relationship between tummy time on plagiocephaly head shape, there is a sig value. -0.889, in the chi square test to test the relationship of spitting up found asymp sig. 0.287 so there is no relationship. While the regression test showed that tummy time had an effect of 72.7% on the frequency of spitting up. Conclusion: There is no relationship between the provision of tummy time on infants' spitting up and plagiocephaly head shape, however, there is an effect on reducing the frequency of spitting up.